An Optimal HVDC Type Study to Increase Wind Power Capacity in Multi-Infeed HVDC Systems - Jung, Seungmin; Yoon, Minhan (International Journal of Engineering and Technology, 2018)
Background/Objectives: The implementation of renewable energy sources such as wind power generators on power system and the use of DC systems that can compensate for unstable characteristics is increasing.Methods/Statistical analysis: In this paper, interaction factor criteria among buses for voltage stability criteria inertia criteria analysis for frequency stability are introduced in case that several HVDC converter stations are installed close to each other. The method has estimated a system stability analysis including stability, reliability, and interaction based on the generator constraints. To calculate available renewable energy capacity, power balance combination analysis has been performed.Findings: Conventional methods for analysis of HVDC system input are generally applied to a single infeed HVDC. In this paper, based on the existing analysis method, we analyze the influence of several and various types of HVDCs on the system and propose must-run generator condition to maintain the stability of the system. Furthermore, the effect on wind power penetration limit was analyzed depending on the combination of HVDC system. The superiority of VSC in multi-infeed HVDC system to promote renewable energy implementation could be estimated through the proposed analysis method.Improvements/Applications: The power system planning and operation including high penetration of renewable energy resources and multi-infeed HVDC system would be performed more appropriately.Â